1997
DOI: 10.1074/jbc.272.42.26550
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Region in Yeast S-II That Defines Species Specificity in Its Interaction with RNA Polymerase II

Abstract: Yeast S-II was found to stimulate yeast RNA polymerase II only and not mouse RNA polymerase II. To identify the molecular region of S-II that defines species specificity, we constructed six hybrid S-II molecules consisting of three regions from yeast and/or Ehrlich cell S-II and examined their activity in terms of RNA polymerase II specificity and suppression of 6-azauracil sensitivity in the yeast S-II null mutant. We found that the region 132-270 (amino acid positions) of yeast S-II is indispensable for spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…The TFIIS of S. cerevisiae is composed of three domains, I, II, and III; the nuclear magnetic resonance structures have been solved for the C-terminal proximal domains II and III (29). Domains II and III are known to be essential for interaction with the RNA polymerase II (1,7,39). S. cerevisiae mutants carrying mutations in the PPR2 gene for TFIIS have been isolated; these mutants show high-level sensitivity to 6AU that inhibits IMP dehydrogenase and ultimately results in limitation in GTP and UTP pools (11).…”
Section: Discussionmentioning
confidence: 99%
“…The TFIIS of S. cerevisiae is composed of three domains, I, II, and III; the nuclear magnetic resonance structures have been solved for the C-terminal proximal domains II and III (29). Domains II and III are known to be essential for interaction with the RNA polymerase II (1,7,39). S. cerevisiae mutants carrying mutations in the PPR2 gene for TFIIS have been isolated; these mutants show high-level sensitivity to 6AU that inhibits IMP dehydrogenase and ultimately results in limitation in GTP and UTP pools (11).…”
Section: Discussionmentioning
confidence: 99%
“…By creating various deletion mutants of S-II, we found that the C-terminal 147 amino acid residues are sufficient for the stimulation of RNA polymerase II and suppression of 6-AU sensitivity (34). Furthermore, by creating chimeric molecules of mouse and yeast S-II, we found that the region between Pro-131 and Phe-270 is responsible for the species-specific interaction of S-II and RNA polymerase II (35). These results suggested that the 6-AU sensitivity of the S-II null mutant is caused by loss of function of S-II as a transcription elongation factor.…”
mentioning
confidence: 93%
“…To investigate the cellular functions of S-II in eukaryotic transcription, we have been studying S-II from yeast (Saccharomyces cerevisiae) (33)(34)(35). The yeast S-II null mutant is viable but becomes sensitive to 6-azauracil (6-AU) 1 (34,36).…”
mentioning
confidence: 99%
“…Domain I, located in the N-terminal region, is involved in interactions with other transcription factors (Saso et al 2003;Wery et al 2004). The other two regions, domain II and domain III, are essential for binding to RNA polymerase II and for both the cleavage and readthrough stimulation activities, respectively (Nakanishi et al 1995;Shimoaraiso et al 1997;Awrey et al 1998). X-ray structure analysis of the yeast RNA polymerase II-S-II complex revealed that domain III of S-II intrudes into the pore of RNA polymerase II and approaches the catalytic center of RNA polymerase II (Kettenberger et al 2003).…”
Section: Structure and Function Of S-ii Involved In Maintaining Transmentioning
confidence: 99%